The Social Dimension of Asynchronous Learning Networks - Wegerif, Rupert (Online Learning, 1998)
This paper argues that the social dimension is important to effectiveness of Asynchronous Learning Networks (ALNs) and needs to be taken into account in the design of courses. Evidence from an ethnographic study of the Teaching and Learning Online (TLO) course offered by the Institute of Education Technology at the Open University is presented in support of this argument. This study found that individual success or failure on the course depended upon the extent to which students were able to cross a threshold from feeling like outsiders to feeling like insiders. Factors affecting the construction of a sense of community are drawn out from interviews with students. The significance of these findings is discussed in relation to a situated model of learning as induction into a community of practice. Finally recommendations are made for the support of community building in the design of courses.